Small Hydro Power Schemes: Technical Aspects - Hira Singh Sachdev; Ashok Kumar Akella (Institute of Advanced Engineering and Science, 2017)
Small hydro systems play a major role in meeting power requirements of remote, isolated, hilly areas in a decentralized manner by tapping water streams, rivulets and canals of small discharge. Small hydroelectric system captures the energy in flowing water and converts it to electricity.Of all the non-conventional renewable energy sources, small hydro stands first as it is more resourceful, reduces system losses, environment friendly, non-consumptive and source is renewable due to their enormous advantages over large hydro and other power plants, lot of small hydro-power plants have come up across the world to meet the ever increasing demand of electrical energy. Lowering the high initial cost of the small hydro-power plants and its popularization is today’s challenges. This paper describes basic techniques design of the small hydro-power development.